On the terms related to spatial ecological gradients and boundaries - Erdős, László (Acta Biologica Szegediensis, 2011)
Ecological gradients and boundaries are currently in the focus of research interest. A widely accepted terminology, however, is still lacking, thus the use of the terms related to gradients and boundaries continues to be confusing. In this paper, we provide new more elaborated definition of the spatial boundary. We distinguish between the gradient (transition) and the space-segment (transitional zone). Our paper identifies the main difference between the two types of gradients: cline and tone. We discuss the meanings of the synonyms boundary line, boundary zone, edge, margin and border. We review the importance of scale and organizational levels in the field of gradients and boundaries. The article also enlightens the difficulties of vegetation mapping associated with boundaries. At last, we identify some important research topics for the future, where intensive studies are needed.